Problems, and Development Priority in Border Area: Muara Tami District, Jayapura - Santosa, Endratno Budi; Musfira, Musfira (TATALOKA, 2025)
The Development from the Edge approach undertaken by the Jokowi administration has significantly impacted the East side of Indonesia's border with Papua New Guinea. While physical improvements and infrastructure development have brought positive changes, they also impacted socio-cultural aspects and created land ownership and usage issues. Transmigration programs applied in this area add complexity, mainly due to the unequal advantages that different communities receive. Understanding these problems is crucial for managing them effectively and guiding the area's development process. This study focuses on Muara Tami District in Jayapura, which has a distinct population and development compared to other areas. This study uses library research, interviews, and the Analytic Hierarchy Process (AHP) method to identify the most significant encountered problems, their causes, and alternative solutions that require immediate implementation. Field observations and secondary data support the analysis, and interviews with stakeholders from various government agencies provide multiple perspectives. The study finds that the transmigration program has more direct and positive impacts on the area than recent national strategic projects. Poor infrastructure services remain a significant issue, while the human resources capabilities aspect becomes a determining factor that helps or hampers better area development. The interviewees also prioritised collaboration among all involved actors to address these issues.